2013
DOI: 10.5120/10655-5421
|View full text |Cite
|
Sign up to set email alerts
|

Architecture for Real Time Monitoring and Modeling of Network Behavior for Enhanced Security

Abstract: Network security is a rapidly growing and is the major area of concern for every network. Firewalls are used as a security check point in network environment even then different types of security issues keep on emerging. In order to protect the network from illegal access, the concept of Intrusion Detection System (IDS) and Intrusion Prevention System (IPS) is been developed. An IDS is a system where the events occurring in a network is monitored and analyzed for identifying the sign of possible incidents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…According to a study by Ambika and Nataraj (2013) on architecture for real-time modelling and monitoring of network behaviour to enhance network security, it was found that the rise in the need for network security has led to the development and application of Intrusion Prevention System (IPS) and Intrusion Detection System (IDS) in network systems to prevent illegal access. An IDS is a system that facilitates monitoring and analysis of events taking place in a network system to identify the signs of possible incidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to a study by Ambika and Nataraj (2013) on architecture for real-time modelling and monitoring of network behaviour to enhance network security, it was found that the rise in the need for network security has led to the development and application of Intrusion Prevention System (IPS) and Intrusion Detection System (IDS) in network systems to prevent illegal access. An IDS is a system that facilitates monitoring and analysis of events taking place in a network system to identify the signs of possible incidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Available monitoring architecture cannot ensure the comprehensiveness of the monitoring data to identify and evaluate all possible problems that could occur in a CN because these architectures are intended to monitor certain aspects of CN performance (e.g., security, productivity, etc.) [3,4] and a specific CN component (e.g., network equipment, network traffic, network services and users).…”
Section: Review Of Workmentioning
confidence: 99%